1976
DOI: 10.1152/ajplegacy.1976.230.6.1461
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder pressure-volume response to gastrointestinal hormones

Abstract: The pressure-volume (PV) response of the opossum gallbladder was studied under basal conditions and after the continuous intravenous infusion of gastrin I, secretin, and cholecystokinin (CCK). The hormone effects were examined individually and in combination. The unstimulated gallbladder was capable of accommodating increases in intraluminal volume with only slight changes in intraluminal pressure. Cholecystokinin significantly increased the pressure recorded from the gallbladder. The pressure generated depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
5

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 0 publications
2
24
0
5
Order By: Relevance
“…Indeed, the nonlinear behaviour is shown in guinea-pig gallbladders (Ryan and Cohen 1976;Bertuzzi et al 1992). The work of (Bertuzzi et al 1992) further showed that such an effect can be significant in gallbladder wall.…”
Section: Introductionmentioning
confidence: 91%
“…Indeed, the nonlinear behaviour is shown in guinea-pig gallbladders (Ryan and Cohen 1976;Bertuzzi et al 1992). The work of (Bertuzzi et al 1992) further showed that such an effect can be significant in gallbladder wall.…”
Section: Introductionmentioning
confidence: 91%
“…25 It has been shown that the active stress of gallbladder smooth muscle due to a stimulus is highly time-dependent 7,56 and probably quite patient specific. 18 Even though the gallbladder pressure-volume response to various continuous intravenous infusions of CCK has been observed 42 and a dynamic method has been proposed for describing gallbladder tone in an in situ baboon model, 43 to date, very few studies have aimed at estimating the action stress in primate gallbladder smooth muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Ali these techniques are based on either perfusion of the gallbladder (85,86,87,89,90) This decrease was manifested by significant reductions in gallbladder contraction amplitude and integrated contraction, which IS a measure of both Ceruletlde is a decapeptide Isolated fram frog skin that has numerous structural similaritles with cholecystokinln(9). In certain animal models, ceruletide has been shown to be as much as ten times more pote nt th an cholecystokinin in inducing gallbladder contraction (9).…”
Section: Spontaneous Gallbladder Activitymentioning
confidence: 99%
“…There exist several in vitro and in vivo models for evaluatlng gallbladder contractility (4,83,84,85,86,87,88,89,90,91 Several invasive in vivo models have been described (83,84,87) Includlng sorne that allow for chronic studies (87,89). Ali these techniques are based on either perfusion of the gallbladder (85,86,87,89,90) Direct measurement of gallbladder tension utilizes simple equipment (83,88).…”
Section: Spontaneous Gallbladder Activitymentioning
confidence: 99%
See 1 more Smart Citation